Chip morphology as a performance predictor during high speed end milling of soda lime glass - Bagum, Mst. Nasima; Konneh, Mohamed; Abdullah, Kasim Abdulrahman. .; Ali, Mohammad Yeakub (Institute of Physics Publishing, 2018)
Soda lime glass has application in DNA arrays and lab on chip manufacturing. Although investigation revealed that machining of such brittle material is possible using ductile mode under controlled cutting parameters and tool geometry, it remains a challenging task. Furthermore, ability of ductile machining is usually assed through machined surface texture examination. Soda lime glass is a strain rate and temperature sensitive material. Hence, influence on attainment of ductile surface due to adiabatic heat generated during high speed end milling using uncoated tungsten carbide tool is investigated in this research. Experimental runs were designed using central composite design (CCD), taking spindle speed, feed rate and depth of cut as input variable and tool-chip contact point temperature (Ttc) and the surface roughness (Rt) as responses. Along with machined surface texture, Rt and chip morphology was examined to assess machinability of soda lime glass. The relation between Ttc and chip morphology was examined. Investigation showed that around glass transition temperature (Tg) ductile chip produced and subsequently clean and ductile final machined surface produced.